1983
DOI: 10.1002/jhrc.1240060806
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between HPLC and NMR properties of some selected alkyl bonded phases

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Many workers have attempted to correlate solute retention with the carbon content of RP stationary phases. Claessens et al (11) and Scott and Kucera (12) linearly correlated k'and percent carbon and corrected retention volume and percent carbon, respectively, for various commercial octadecyl and octyl columns. Shaikh and Tomaszewski (13) found a linear relationship between k' and carbon loading for seven commercial octadecyl packings whereas Engelhardt and Ahr (14) noted linearity between log A'and percent carbon for four commercial octadecyl phases.…”
mentioning
confidence: 99%
“…Many workers have attempted to correlate solute retention with the carbon content of RP stationary phases. Claessens et al (11) and Scott and Kucera (12) linearly correlated k'and percent carbon and corrected retention volume and percent carbon, respectively, for various commercial octadecyl and octyl columns. Shaikh and Tomaszewski (13) found a linear relationship between k' and carbon loading for seven commercial octadecyl packings whereas Engelhardt and Ahr (14) noted linearity between log A'and percent carbon for four commercial octadecyl phases.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the usefulness of solution-state nuclear magnetic resonance (NMR) spectroscopy in the investigation of molecular interactions in RPLC systems. However, many of these studies were performed with uncommon solvents or only encompassed a narrow range of binary compositions. ,,, Previous work in our laboratory 2-4 has indicated that, with an appropriate wetting procedure for the stationary phase, the entire binary composition range for hydro-organic mixtures of acetonitrile and methanol becomes accessible for study via solution-state deuterium ( 2 H) NMR.…”
mentioning
confidence: 99%